Control engineering : MATLAB Exercises. - Keviczky, László (Advanced Textbooks in Control and Signal Processing, 2019)
This MATLAB exercise book accompanies the textbook Control Engineering, providing a platform for students to practice problem solving in the analysis and design of continuous and discrete control problems reflected in the main textbook. The book starts off with a brief introduction to MATLAB, control toolbox and Simulink. Subsequent chapters include a short theoretical summary of the topic followed by exercises on solving complex problems using MATLAB commands. These exercises are ideal for students in computer laboratory classes.